2014
DOI: 10.1167/iovs.13-12853
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum 25-Hydroxyvitamin D Is Associated With Myopia in Korean Adolescents

Abstract: Purposes: To assess the relationship between serum level of 25-hydroxyvitamin D (25(OH)D) and refractive error in Korean adolescents. Methods: A total of 2,038 adolescent aged 13-18 years, who participated in the Korea National Health and Nutrition Examination Survey (KNHANES) from 2008 to 2011 underwent refractive examination using an autorefractor. Serum 25(OH)D concentration and other potential risk factors were examined. Multivariate regression analysis was performed to investigate the association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
81
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 35 publications
9
81
1
2
Order By: Relevance
“…12 However, it remains unclear which of the numerous elements associated with time spent outdoors, such as light intensity, ultraviolet radiation (UVR), or distant focus, confers the reduced risk of myopia. Vitamin D concentrations have been inversely associated with myopia in some but not all studies, [13][14][15][16][17] while genetic polymorphisms in vitamin D pathway genes have been associated in 1 study but not in another. 13,17 We exploited the availability of relevant existing information (ie, refractive status, UVR, education, serum vitamin D concentrations, and genetic polymorphisms in vitamin D pathway genes) in the European Eye Study with the objective of investigating their association with myopia.…”
mentioning
confidence: 96%
“…12 However, it remains unclear which of the numerous elements associated with time spent outdoors, such as light intensity, ultraviolet radiation (UVR), or distant focus, confers the reduced risk of myopia. Vitamin D concentrations have been inversely associated with myopia in some but not all studies, [13][14][15][16][17] while genetic polymorphisms in vitamin D pathway genes have been associated in 1 study but not in another. 13,17 We exploited the availability of relevant existing information (ie, refractive status, UVR, education, serum vitamin D concentrations, and genetic polymorphisms in vitamin D pathway genes) in the European Eye Study with the objective of investigating their association with myopia.…”
mentioning
confidence: 96%
“…However, as it is difficult to prove that an exposure has no effect at all (e.g. the effect is very small to be detected), we show that if it exists it should be in the range of A study from Choi et al [136] involving 2038 adolescents from South Korea showed a significant association between 25(OH)D concentrations and RE; however, time spent outdoors was not entirely accounted for (i.e. physical exercise and area of residence were investigated but not outdoor time).…”
Section: 382 For Europeans and N= 8376 From Asians) From Cream [1mentioning
confidence: 60%
“…Also, epidemiological studies have shown association between refractive error and anthropometric traits and smoking [136,299]. In order to investigate potential pleiotropic effects, we performed a series of regressions between the educational attainment PGRS and BMI, height and smoking in the BMES cohort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations